Beyond Honor and Shame: An Indigenous Psychology Reconstruction of Siri’ na Pacce as a Relational Moral Regulation System - Piara, Muhrajan; Islah, Fadhil Maliky; Hidayati, Nurul; Fikri, Aldinel; Akhdisholikhah, Riza (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
This study aims to reconstruct siri’ na pacce as a relational moral regulation system within the reflective academic interpretations of Bugis and Makassar cultural values. Using an interpretive qualitative design within an indigenous psychology framework, data were collected through in-depth interviews with seven interdisciplinary academic respondents. The data were analyzed using Reflexive Thematic Analysis. The findings identified four main themes: siri’ na pacce as a unified system of humanitarian ethics, siri’ as dignity, integrity, and ethical self-regulation, pacce or pesse as empathic concern, solidarity, and relational repair, and the supporting values and contemporary challenges surrounding its practice. The study shows that siri’ na pacce should not be reduced to a static cultural inheritance, a simple concept of shame, or a symbolic marker of ethnic identity. Rather, it operates as a humanizing ethical system in which dignity and empathy function as mutually corrective moral regulators. The findings also indicate that siri’ na pacce is vulnerable to contemporary distortion when siri’ is reduced to prestige, aggression, or reactive defensiveness, and when pacce is weakened by individualism, dishonesty, weakened transmission, and digital provocation. This study provides emic conceptual reconstruction of dignity, empathy, relationality, and moral regulation from the Global South.